Analysis of the Dynamics of a Two-Degree-of-Freedom Nonlinear Mechanical System under Harmonic Excitation - Cheib, Akram Khalil; Puzyrov, V. E.; Savchenko, N. V. (Nonlinear Dynamics and Systems Theory, 20 (2) (2020),, 2020)
In this paper the 2-degree-of-freedom mechanical system under the action of external harmonic excitation is considered. The system consists of the rotating elastically mounted frame and attached mass (absorber) with viscous friction and nonlinear stiffness. The stability problem of periodic regimes is investigated based on the averaging method. The influence of nonlinear component is analyzed with respect to responses of the main mass in the vicinity of resonance frequencies.
Keywords: harmonic excitation; averaging technique; resonance frequency; stability; nonlinear stiffness